In vivo multiphoton microscopy technique to reveal the physiology of the mouse placenta. - Zenclussen, A; Olivieri, D; Dustin, M; Tadokoro, C (2012)
PROBLEM: Pregnancy is a challenge to the maternal immune system as it must defend the body against pathogens while at the same time develop immune tolerance against the fetus growing inside the uterus. Despite ex vivo techniques being used to understand these processes, in vivo techniques are missing. METHOD OF STUDY: To directly study these phenomena, we have developed a new microscope stage and surgical procedures for use in two-photon microscopy, for in vivo observation of the mouse placenta. RESULTS: These tools and surgical procedures demonstrate fetal and maternal blood flow inside the labyrinth zone of the placenta, as well as its three dimensional structure. It was also useful to identify Plasmodium chabaudi-infected red blood cells inside this labyrinth zone. CONCLUSION: We believe this technique will represent an important contribution for expanding the available knowledge concerning cell dynamics and interactions at the fetal-maternal interface.